2016
DOI: 10.5812/archcid.39318
|View full text |Cite
|
Sign up to set email alerts
|

Association Between IL12A rs568408, IL12B rs3212227 and IL-12 Receptor rs383483 Polymorphisms and Risk of Pulmonary Tuberculosis

Abstract: Background: Interleukine-12 (IL-12) induced interferon-γ (IFN-γ) production and development of T cells into Th1 cells, which has a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…We investigated the impact of IL12A rs568408 gene polymorphisms on risk pulmonary tuberculosis in a sample was living in southeast (13) . The IL12A rs568408 variant was not a risk factor for susceptibility to pulmonary tuberculosis in codominant, dominant and recessive tested inheritance models (11) , but another study showed association between IL12A rs568408 polymorphisms and risk of pulmonary tuberculosis in Chinese population and It was found that genetic variants AG/GG of rs2243115 (IL12A) were associated with a decreased risk of pulmonary tuberculosis (12) .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We investigated the impact of IL12A rs568408 gene polymorphisms on risk pulmonary tuberculosis in a sample was living in southeast (13) . The IL12A rs568408 variant was not a risk factor for susceptibility to pulmonary tuberculosis in codominant, dominant and recessive tested inheritance models (11) , but another study showed association between IL12A rs568408 polymorphisms and risk of pulmonary tuberculosis in Chinese population and It was found that genetic variants AG/GG of rs2243115 (IL12A) were associated with a decreased risk of pulmonary tuberculosis (12) .…”
Section: Discussionmentioning
confidence: 98%
“…Polymorphism of IL12A gene (G/A rs568408 genotype) was examined by using Tetra-ARMS-PCR technology. The PCR reaction was carried out on a DNA template with a pair of specific primers (Alpha DNA, Canada) that designed according to (11) . Table (1), 20 μl was the total volume of reaction mix (PioNeer, Korea), and the molecular marker size (Promega, USA) 100-2000 base pair.…”
Section: Genotyping Of Il12a Gene (G/a Rs568408 Genotype)mentioning
confidence: 99%
“…A crucial cytokine in the fight against intracellular infections, interleukin-12, encourages the growth of Th1 cells, cell-mediated cytotoxicity, and IFN-gamma production [ 16 ]. Various studies have shown that the two genes that code for IL-12, IL12A, and IL12B, have numerous functional polymorphism sites that may have an impact on the development and spread of lung cancer [ 17 ] and tuberculosis [ 18 ]. Tan et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of the southeast Iranian population, research revealed that IL12A rs568408, polymorphism was not a significant genetic determinant for resistance or susceptibility to pulmonary tuberculosis. In patients and controls, the rates of the GA and AA genotypes of the IL12A rs568408 variation were 38.5%, 1.7%, and 37.3%, 1.1%, respectively [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 IL-12 has been shown to inhibit the proliferation and metastasis of various malignant tumors, in vitro and in vivo, 10 and to inhibit the differentiation of natural killer and Th2 T helper cells, contributing to a strong anti-tumor effect. 11 IL-12 is encoded by two genes, IL12A and IL12B, and numerous studies have demonstrated that the IL12A and IL12B genes include multiple functional polymorphic sites that might affect the occurrence and progression of non-Hodgkin lymphoma, 12 tuberculosis, 13 autoimmune disease, 14 gastric carcinoma, 15 lung carcinoma, 16 and other malignancies. 17 Tan et al showed that the IL12A rs568408 variant may be a marker single-nucleotide polymorphism (SNP) associated with an increased risk of poor HBV clearance and HBV-related HCC development.…”
Section: Introductionmentioning
confidence: 99%